2007
DOI: 10.1007/s11136-007-9195-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting quality of life impairment in chronic schizophrenia from cognitive variables

Abstract: This study suggests that deficits in executive functioning, attention, memory and motor skills substantially contributes to predicting impairments across a wide range of HRQL domains, and, consequently, to quality of life appraisal in schizophrenia. Cognitive predictors cannot be attributed to illness-related and background variables. It can be concluded that, when aiming at the improvement of quality of life in schizophrenia patients, cognitive functioning should be targeted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
3
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 36 publications
6
35
3
3
Order By: Relevance
“…The tests were performed one-tailed, and power calculations showed that the power for the t-test to detect a mean difference between controls and patients amounting to a medium effect size (Cohen's d 00.5) was b 00. 48 with an a error of 5% (one-tailed), and for a large effect size (Cohen's d 00.8) the power was b00.82. We also used bootstrap techniques to create 1000 Spearman's rank correlation samples to investigate the relation between TEA and BADS performance scores and symptom ratings (BPRS), medication (percent of maximum dose) and length of illness.…”
Section: Discussionmentioning
confidence: 99%
“…The tests were performed one-tailed, and power calculations showed that the power for the t-test to detect a mean difference between controls and patients amounting to a medium effect size (Cohen's d 00.5) was b 00. 48 with an a error of 5% (one-tailed), and for a large effect size (Cohen's d 00.8) the power was b00.82. We also used bootstrap techniques to create 1000 Spearman's rank correlation samples to investigate the relation between TEA and BADS performance scores and symptom ratings (BPRS), medication (percent of maximum dose) and length of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous research groups have investigated the relation between QOL and cognitive function in people with schizophrenia, and reported the significant correlations between QOL and some domains of cognitive function such as verbal memory, vocabulary, fluency performance, attention, social knowledge, and executive function (12,28,(29)(30)(31)(32).…”
Section: Relation Between Cognitive Func-tion and Quality Of Lifementioning
confidence: 99%
“…Neurocognitive impairment has been found to limit creativity, work performance, quality of life, selfesteem, and psychosocial functioning substantially in patients with other severe mental illnesses, especially schizophrenia (16)(17)(18)(19)(20)(21). In BPD, there has been increasing recognition of more functional impairment than had been realized formerly, particularly with regard to independent living, personal relationships, and vocational success (22).…”
mentioning
confidence: 99%
“…However, in a recent review of 15 studies, Bauer and colleagues (26) found that, except for ongoing depressive symptoms, few of these factors were consistently associated with poor functional outcomes across studies. Neurocognitive functioning, remarkably, was not examined in most of the preceding studies of BPD patients, despite having been explored extensively in relation to functional disability in patients with schizophrenia and other neuropsychiatric conditions (17)(18)(19)(20)(21)27).…”
mentioning
confidence: 99%